Structural, Optical, and Electrical Properties of Pure α-Al2O3 Nanopowders with Add V2O7 and Cu2O by Sol-Gel Method: الخصائص التركيبية والضوئية والكهربائية لمساحيق α-Al2O3 النانوية النقية مع إضافة V2O7 وCu2O بطريقة سوجل - S. Al-Ariki1, M. A. Ali. AL-Mushaki1 and Shakib Moqbel Alsowidy2 (Journal of the Faculty of Education, 2024)
This manuscript explored the synthesis and comprehensive characterization of pure α-Al2O3 and (α-Al2O3)8-x(V2O7)20(Cu2O)x at varying molar ratios (x = 1%, 2%, and 3%) in nanopowder form, prepared using the sol-gel method. After subjecting the samples to heat treatment, X-ray diffraction (XRD) revealed their high crystallinity. The crystallite size was calculated using the Scherrer formula, exhibited variations among the samples with pure α-Al2O3 possessing a size of 43.10 nm and the mixed oxide nanopowders falling within the range of 29.54 nm to 34.84 nm. These materials displayed semiconductor characteristics, with band gap values ranging from 3.28 eV to 5.21 eV. Moreover, as the molar concentration of copper increased, electrical conductivity improved, signifying potential applications in systems requiring regulated electrical behavior. These findings highlight the versatility of these materials, offering opportunities for tailored crystallinity, band gap tuning, and controlled electrical properties, making them suitable for diverse technological and scientific applications.